2024
DOI: 10.2147/dmso.s448638
|View full text |Cite
|
Sign up to set email alerts
|

A Gender-, Age-, and Weight Status-Specific Analysis of the High Prevalence of Hyperuricemia Among Chinese Children and Adolescents with Obesity

Meijuan Liu,
Bingyan Cao,
Qipeng Luo
et al.

Abstract: To explore the gender-, age-, and weight status-specific prevalence of hyperuricemia (HUA) and its associated risk factors among Chinese children and adolescents with obesity. Methods: A total of 1329 children aged 2-17 years, who were diagnosed with obesity and hospitalized in our center from January 2016 to December 2022 were recruited. They were divided into mild obesity, moderate obesity, and severe obesity groups. HUA was defined as fasting serum uric acid level >420 μmol/L for boys and >360 μmol/L for gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Thus far, various studies worldwide have identified different risk factors associated with the occurrence of HUA, such as age, gender, waist circumference, drinking, smoking, obesity, hypertension, dyslipidemia and triglyceride-glucose index ( Dong et al, 2022 ; Piao et al, 2022 ; Wang et al, 2022 ; Ding et al, 2023 ; Lyu et al, 2023 ; Teramura et al, 2023 ; Liu et al, 2024 ). Moreover, several prediction models for HUA have been developed using machine learning algorithms ( Lee et al, 2019 ; Zeng et al, 2020 ; Gao et al, 2021 ; Huang et al, 2022 ; Zhu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, various studies worldwide have identified different risk factors associated with the occurrence of HUA, such as age, gender, waist circumference, drinking, smoking, obesity, hypertension, dyslipidemia and triglyceride-glucose index ( Dong et al, 2022 ; Piao et al, 2022 ; Wang et al, 2022 ; Ding et al, 2023 ; Lyu et al, 2023 ; Teramura et al, 2023 ; Liu et al, 2024 ). Moreover, several prediction models for HUA have been developed using machine learning algorithms ( Lee et al, 2019 ; Zeng et al, 2020 ; Gao et al, 2021 ; Huang et al, 2022 ; Zhu et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%